Networks, experts and the internationalization of education policies - Eneida Oto Shiroma (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2020)
This paper discusses the regional policy networks relevance for studies about the international local agendas alignment. The reform isomorphism adopted in different countries led us to research the borrowing policies phenomenon. We investigated an experts network invited by Unesco to develop a regional project on teaching policies for the Latin America. We analyzed their members, institutional filiations, documents and proposals. We mapped the previous expert participation in international organizations, political charge in State, universities and their joint actions. The network ethnography allowed us to point out the public-private permeability. Our approach highlighted that experts, engaged in regional networks disseminate their ideas, promote a policies international circulation and contribute for building the active reception of their recommendations at a local level. Mapping networks proves to be a fruitful methodological resource to investigate the policymaking complex process and experts role on establishing the Education agenda.